2020
DOI: 10.31234/osf.io/k5emn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patterns of Mutual Exclusivity and Retention: A Study of Monolingual and Bilingual 2-Year-Olds

Abstract: When children learn their native language, they tend to treat objects as if they only have one label—a principle known as mutual exclusivity (ME). However, bilingual children are faced with a different cognitive challenge—they need to learn to associate two labels with one object. In the present study, we compared bilingual and monolingual 24-month-olds' performance on a challenging and semi-naturalistic forced-choice referent selection task and retention test. Overall, both language groups used ME at similar … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
(68 reference statements)
1
2
0
Order By: Relevance
“…Because bilinguals' knowledge of translation equivalents inherently violates mutual exclusivity, studies have examined whether bilinguals adhere to mutual exclusivity less than monolinguals (e.g., Frank & Poulin-Dubois, 2002;Kalashnikova et al, 2019). However, in line with previous work on a similar age range (Frank & Poulin-Dubois, 2002;Kalashnikova et al, 2019;Rocha-Hidalgo et al, 2021), we found no difference in adherence to mutual exclusivity between monolinguals and bilinguals, as well as no evidence of a relation between bilinguals' knowledge of translation equivalents and adherence to mutual exclusivity (cf. Byers-Heinlein & Werker 2013).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Because bilinguals' knowledge of translation equivalents inherently violates mutual exclusivity, studies have examined whether bilinguals adhere to mutual exclusivity less than monolinguals (e.g., Frank & Poulin-Dubois, 2002;Kalashnikova et al, 2019). However, in line with previous work on a similar age range (Frank & Poulin-Dubois, 2002;Kalashnikova et al, 2019;Rocha-Hidalgo et al, 2021), we found no difference in adherence to mutual exclusivity between monolinguals and bilinguals, as well as no evidence of a relation between bilinguals' knowledge of translation equivalents and adherence to mutual exclusivity (cf. Byers-Heinlein & Werker 2013).…”
Section: Discussionsupporting
confidence: 79%
“…One is a familiar object for which the child knows the label (e.g., cup), and one is an unfamiliar object for which the child does not have a label (e.g., avocado slicer)-and asked to identify whether the familiar object or the unfamiliar object is the referent of a novel label (e.g., "Give me the blick," or "Blick!"). The manner in which children are asked to select an object varies across studies, with some studies using eye-tracking or looking-while-listening paradigms in which children look at the target object (e.g., Byers-Heinlein & Werker, 2009;Houston-Price et al, 2010;Kalashnikova et al, 2018) and others using behavioral paradigms in which children point to or hand the target object to an experimenter (e.g., Byers-Heinlein et al, 2014;Davidson & Tell, 2005;Frank & Poulin-Dubois, 2002;Kalashnikova et al, 2015;Rocha-Hidalgo et al, 2021).…”
Section: Mutual Exclusivity Word Disambiguation Tasksmentioning
confidence: 99%
“…A second possibility suggested by Kremin and Byers-Heinlein, (2021) is that researchers could combine both a binary categorization and a continuous approach when reporting their results (see following examples: Rocha-Hidalgo et al, 2020;Kalashnikova et al, 2021). Categorization approaches could also be improved.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%